STUDENTS ENGAGEMENT IN LEARNING MATHEMATICS WITH THE ACADEMIC PERFORMANCE OF ELEMENTARY SCHOOL - Ratri Nuryani Qudwatullathifah; Amanda Maharani; Cucuh Miftahurrohmah (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
Mathematics learning at the elementary school level plays a crucial role in developing students’ logical, critical, and analytical thinking skills. Effective mathematics instruction is supported by several factors, one of which is student engagement. Student engagement is a key factor that influences learning outcomes, including academic performance. This study aims to examine the relationship between student engagement in mathematics learning and their academic performance. A quantitative method with a descriptive and correlational approach was used. The study population consisted of 4th and 5th grade students at SDN 3 Kramat, and total sampling was employed, resulting in a sample size of 64 students. The data analysis revealed a significant relationship between student engagement in mathematics learning and academic performance, with a significance value of 0.000 (< 0.05) and a correlation coefficient of 0.519. This indicates a moderate, positive relationship between the two variables.